Pengendalian Kualitas UMKM Bagus Bakery dengan Mengunakan Metode Seven Tools - Suwarno, Agus; Rahardjo, Sugeng Budi (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Quality is the most important factor for a product. The failure rate in the production process that is not in accordance with predetermined standards is a measure of the quality and effectiveness of production. Likewise for the production of UMKM Bagus Bakery which has a production failure rate or NG product of 184 of the total production of 4610 pieces or 3.99%. Based on fishbone diagram analysis, the causes of production process failure are material composition, unsanitary environment, oil temperature. The test results based on the seven tools method of overcoming bantet bread using fermipan to 10 grams and bread improver 15 grams, cleaning the equipment every time the dough is made, the oil temperature between 165 175 Â°C produces the smallest production failure value.